PENGARUH IBU BEKERJA DENGAN PERKEMBANGAN EMOSI ANAK USIA 4-6 DI KELURAHAN VI SUKU KOTA SOLOK - Sari, Desi Fatmayeni Ferdial; Nurhafizah, Nurhafizah (Prodi PG-PAUD, FKIP, Universitas Trilogi, 2019)
Abstract: The Influence of Working Mothers with Emotional Development of Children 4-6 Years in Kelurahan VI of Solok City Tribe This study aims to obtain information about how much influence Mother works with emotional development of children aged 4-6 years in Kelurahan VI Solok City Tribe. Hypothesis proposed research there is an influence of working mother with the emotional development of children aged 4-6 years in the village VI tribe of Solok. This type of research is descriptive with a quantitative approach describing how much influence Mother works with emotional development of children aged 4-6 years in Kelurahan VI Solok City Tribe. The instrument of this study was a Likert Scale model questionnaire that had been tested for validity and reliability using the SPSS 16 application. The number of respondents in this research were 50 working mothers in Kelurahan VI of Solok City, taken using the purposive sampling technique. The results showed that there was an influence from working mothers with emotional development of children aged 4-6 years in Kelurahan VI of Solok City by 30%.